Kapitalisme Global sebagai Akar Kerusakan Lingkungan: Kritik terhadap Etika Lingkungan - Yohanes Hasiholan Tampubolon; Dreitsohn Franklyn Purba (Reformed Center for Religion and Society, 2022)
In the middle of environmental crisis context, the debate on the definition and concept of environmental ethics seems that there will be no end. This paper wants to assess major impact on the reality of environmental damage. Through the literature review method, the author finds that environmental crisis does not come from a person's bad ethics, but there is another factor that also influences environmental crisis, namely global capitalism. Capitalism is a mode of production and consumption which is the main actor of environmental crisis. It does not mean that destructive behavior is done by humans not need to be morally condemned, on the other hand the tendency of moralism is needed to be avoided, which assumes that environmental problem can be solved by producing environmental ethics ideas that are friendly to all nature.